Genome-wide identification and functional analysis of CYP450 genes in eggplant (Solanum melongena L.) with a focus on anthocyanin accumlation - Ting Yang; Ruijie Zhuang; Shiyu Wang; Wanping Lv; Yongxian Wen (BMC Genomics)
Abstract Background In plants, Cytochrome P450 (CYP450) constitutes the largest family of metabolic enzymes and plays a crucial role in various physiological processes, including plant growth and development. Eggplants are well-known for their peel’s high concentration of anthocyanin compounds that provide significant health benefits to humans. The accumulation of anthocyanins in eggplant peels is an important process during growth and development. Therefore, it is essential to identify the CYP450 genes in eggplant (SmCYPs) and analyze their expression profiles during the period of anthocyanin accumulation in the peel. Results A total of 180 SmCYPs were identified in the eggplant genome and classified into eight subfamilies based on phylogenetic analysis. These SmCYPs exhibited highly conserved gene structure (exon/intron) and protein motifs, especially within their respective subgroup. Sixteen pairs of genes with collinearity were identified through gene duplication analysis. Promoter cis-acting element analysis revealed that SmCYPs are involved in various responses, including growth and development, stress responsiveness, and light responsiveness. Transcriptome data analysis revealed that all SmCYPs were expressed in various eggplant tissues, such as roots, stems, leaves, flowers, and fruits; with diverse expression patterns among members. The expression patterns of SmCYPs in eggplant peel also exhibited diversity during different stages of anthocyanin accumulation. qRT-PCR analysis demonstrated similar expression patterns for 15 selected SmCYPs as observed in the transcriptome data. Metabolomics analysis further suggested that SmCYPs are involved in the biosynthesis of secondary metabolites and metabolic pathways related to flavonoid and flavone/flavonol biosynthesis. Notably, three specific SmCYPs (SmCYP73A1/75A/98A1) play a significant role in flavonoid biosynthesis, particularly in anthocyanin synthesis in eggplant. Conclusion Genome-wide identification, phylogenetic analysis, expression profile analysis, and exploration of metabolic pathways related to SmCYPs provide valuable insights into the roles of these genes in anthocyanin accumulation in various tissues and organs, including eggplant peel. The findings from this study lay a foundation for the functional analysis of SmCYPs involvement in anthocyanin accumulation in eggplant peel, providing a molecular basis for breeders to cultivate novel varieties of eggplants with high levels of anthocyanin content.